PENGARUH INFORMATION ASYMMETRY, EARNING MANAGEMENT, VOLUNTARY DISCLOSURE, DAN FIRM SIZE TERHADAP COST OF EQUITY PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016 - 2020 - Manalu, Renata Agnessya; Hidayat, Taufiq (Journal of Accounting, Management and Islamic Economics, 2024)
The purpose of this study was to examine the effect of information asymmetry, earning management, voluntary disclosure, and firm size on cost of equity. Furthermore, this study examines the relationship of independent variables to the dependent variable. Information asymmetry is proxied by bid-ask spread, earning management is proxied by discretionary accruals, voluntary disclosure is proxied by index which refers to discretionary financial and non-financial information, and firm size is proxied by total assets. The multiple linear regression method with the Ordinary Least Square (OLS) technique was used to test the effect of independent variables on the dependent variable. A total of 20 State-owned companies listed from 2016 to 2020 were sampled in this study. The result of this study found that information asymmetry has no significant effect on cost of equity, earning management has no negative significant effect on cost of equity, voluntary disclosure has a positive significant on cost of equity, and firm size has a positive significant on cost of equity.